GEOTHERMAL SYSTEM CONCEPTUAL MODEL UPDATE BASED ON GEOSCIENCE AND EXPLORATION WELL DATA OF ERTANKIAN GEOTHERMAL FIELD, WEST JAVA, INDONESIA - Vita Aprilina, Nur
Geoscience surveys have been conducted in Gunung Salak during 1982-1983 and were able to identify five geothermal prospects. Exploration wells were drilled in two of the most attractive prospect areas, namely the Awibengkok and Ertankian Fields. Exploration wells in Awibengkok showed a better result that further studies of Ertankian Prospect were never carried out. Currently Star Energy Geothermal, Ltd. conduct an inventory program of all potentials which can be developed within the Awibengkok WKP. Ertankian is one of the prospects being re-evaluated. Therefore, this research is important to understand the Ertankian Geothermal System and update the conceptual model. The research is conducted by integrating geological, geochemical, geophysical, and well data analysis. Geological analysis is carried out to identify the components of geothermal system and estimate the system boundaries. This includes DEM analysis, XRD analysis, petrography, and methylene blue analysis on cutting and core samples. Geochemical studies of water and gas were carried out to understand the fluid type, reservoir characteristics, determination of outflow and upflow, and their relationship to the Awibengkok Reservoir. Geophysical studies which include interpretation of magnetotelluric and gravity data were conducted to delineate the geothermal system. The GGG study was then validated and integrated with the well data. The results of the research show that the Ertankian System is a separate system from Awibengkok which is indicated by a discontinuous claycap geometry. SE and Ciganea faults are also interpreted to be system boundaries. In addition, the Ertankian System develops in different volcanostratigraphic and geomorphological units, hence it has its own geothermal system component. The upflow is in the Ertankian Crater and in the ERT-1 Well area, while the outflow is in the Cikuluwung Hot Spring, which has bicarbonate-chloride type. The reservoir fluid is neutral chloride water, equilibrium, and high temperature (260?-300?C). Ertankian reservoir is composed of andesite lava rock, pyroclastic, marl, limestone, and microdiorite intrusion. Well ERT-1 shows a convective temperature profile, good indication of permeability, and a commercial geothermal reservoir. Therefore, Ertankian Prospect has a potential to be developed.